2018
DOI: 10.1590/0037-8682-0220-2017
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a packaging cell line for pseudo-infectious yellow fever virus particle generation

Abstract: Introduction: Pseudo-infectious yellow fever viral particles (YFV-PIVs) have been used to study vaccines and viral packaging. Here, we report the development of a packaging cell line, which expresses the YFV prM/E proteins. Methods: HEK293 cells were transfected with YFV prM/E and C (84 nt) genes to generate HEK293-YFV-PrM/E-opt. The cells were evaluated for their ability to express the heterologous proteins and to package the replicon repYFV-17D-LucIRES, generating YFV-PIVs. Results: The expression of prM/E p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Ultimately, HEK293T cells were selected, as these cells maintained their high viral titers even in the presence of observable cytopathic effects. HEK293 cells are commonly used as a platform for the propagation or production of flavivirus VLP vaccines (Powers et al, 2022;Queiroz et al, 2018), adenovirus-based COVID-19 vaccines (Joe et al, 2022), and studying permissive to persistent flavivirus infections (Mlera et al, 2015(Mlera et al, , 2016Sempere & Arias, 2019). Contrary to earlier reports of TMUV sensitivity to human interferon (Ma et al, 2019) and the moderate susceptibility to TMUV infection reported for HEK293T cells (Ruangrung et al, 2021), our experiments demonstrate an early onset of virus propagation and high virus titers at 72 hpi.…”
contrasting
confidence: 82%
“…Ultimately, HEK293T cells were selected, as these cells maintained their high viral titers even in the presence of observable cytopathic effects. HEK293 cells are commonly used as a platform for the propagation or production of flavivirus VLP vaccines (Powers et al, 2022;Queiroz et al, 2018), adenovirus-based COVID-19 vaccines (Joe et al, 2022), and studying permissive to persistent flavivirus infections (Mlera et al, 2015(Mlera et al, , 2016Sempere & Arias, 2019). Contrary to earlier reports of TMUV sensitivity to human interferon (Ma et al, 2019) and the moderate susceptibility to TMUV infection reported for HEK293T cells (Ruangrung et al, 2021), our experiments demonstrate an early onset of virus propagation and high virus titers at 72 hpi.…”
contrasting
confidence: 82%